2017
DOI: 10.3390/su9040496
|View full text |Cite
|
Sign up to set email alerts
|

Economic City Branding in China: the Multi-Level Governance of Municipal Self-Promotion in the Greater Pearl River Delta

Abstract: Abstract:In the urban development policy in China, city brands play an important role in setting targets for Chinese cities. These economic city brands, however, are not produced in an institutional vacuum: they are embedded in the visions national, provincial and municipal governments have for these cities, i.e., on multi-level governance. In this paper, a data-intense analysis of economic city branding practices has been conducted in the Greater Pearl River Delta, taking into account national, provincial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 57 publications
(67 reference statements)
3
35
0
Order By: Relevance
“…This is different from what is often understood as city branding as a targeted process in which labels, slogans and logos are established which are subsequently broadly advertised across the media [23]. We utilize an analytical framework on urban developmental pathways that explicitly relates to urban and industrial profiles cities have and examine how their existing geographic profiles compare with their desired brands and pathways [9,13]. The alignment of past traditions, status quo and future ambitions is examined by comparing city branding practices adopted by cities with their urban and industrial developmental pathways.…”
Section: City Branding: Theory and Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…This is different from what is often understood as city branding as a targeted process in which labels, slogans and logos are established which are subsequently broadly advertised across the media [23]. We utilize an analytical framework on urban developmental pathways that explicitly relates to urban and industrial profiles cities have and examine how their existing geographic profiles compare with their desired brands and pathways [9,13]. The alignment of past traditions, status quo and future ambitions is examined by comparing city branding practices adopted by cities with their urban and industrial developmental pathways.…”
Section: City Branding: Theory and Methodologymentioning
confidence: 99%
“…Each of these concepts reflect a desired shift in the direction of ecological modernization where social, economic and ecological gains are presumed to come nicely together. Earlier studies in the application of city branding among cities in the face of ecological modernization focused on polycentric regions such as Rhine-Ruhr in Germany and Randstad in The Netherlands [11] and the three Chinese Mega-City Regions Pearl River Delta, Yangtze River Delta and Jin-Jin-Ji [12][13][14]. From these studies, it appeared that city branding practices were quite commonly used but that cities with a strong tradition in manufacturing and heavy industry were reluctant to present themselves as such and preferred to dress up as service or innovation cities even if this seemed barely realistic in the eyes of their stakeholders.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang and Zhao [49] found that city branding identity differentiates a given city from other cities by combining its spatial configuration and cultural values in a complex way. On the other hand, Lu, de Jong and Chen [50] focused on desired economic city branding and stressed a number of elements including features and beneficial attributes and as the core element of a brand, identity reflects how producers want city branding to be perceived by the outside world.…”
Section: Local Brand Valuementioning
confidence: 99%